Quercetagetin alleviates inflammatory osteoclastogenesis and collagen antibody-induced arthritis via Nrf2 signaling and Pten/AKT/Nfatc1 axis - Wang, Haojue; Yuan, Tao; Wang, Jingpeng; Li, Dengju; Lee, Wayne Yuk-wai; Li, Ziqing; Sun, Shui (Arthritis research & therapy, 2025)
Purpose Quercetagetin, a flavonoid derived from the natural herb Flos eriocauli, is used in traditional Chinese medicine for its fire-purging (anti-inflammation) and wind-expelling (pain-alleviating) properties. However, its potential effects concerning rheumatoid arthritis (RA) remain underexplored. This study was designed to elucidate the potential associations between Quercetagetin and RA, establishing the therapeutic potential of Quercetagetin and related mechanisms in RA treatment. Methods Network pharmacology was conducted to decipher related targets and signaling pathways between Quercetagetin and RA. In vitro assays were then conducted to explore the effects of Quercetagetin on osteoclast cell behaviors and corresponding signaling pathways. In vivo study further validated the therapeutic effect of Quercetagetin in collagen antibody-induced arthritis (CAIA) mice. Results The network pharmacological analysis indicated an intimate correlation of Quercetagetin with RA-related inflammatory osteolysis treatment. Pertaining to biological validations, 2 µM of Quercetagetin successfully inhibited LPS-driven osteoclast differentiation and function. qPCR assay and Western blot analyses denoted parallel changes in osteoclastic marker genes and proteins. Further mechanism study uncovered the effect of Quercetagetin in stimulating the Nrf2/Keap1 signaling pathway and moderating the Pten/AKT/Nfatc1 axis in osteoclasts. In vivo study revealed 40 mg/kg Quercetagetin every day could significantly relief joint destruction in CAIA mice. Conclusions Our study presents Quercetagetin ‘s therapeutic potential in treating RA, outlining its effects and potential mechanisms in suppressing LPS-induced osteoclast activity, and alleviating inflammatory bone destruction in CAIA model, thereby laying the groundwork for further translational research on Quercetagetin and Flos eriocauli in RA treatment. Highlights Quercetagetin extracted from Flos eriocauli displayed brilliant anti-osteoclast and anti-inflammation potential during rheumatoid arthritis. Quercetagetin significantly repressed lipopolysaccharide-stimulated osteoclast behavior from phenotypical and molecular level. Quercetagetin mitigated inflammatory bone destruction in collagen antibody-induced arthritis.